Observation of early childhood educators’ interaction style and child experience: opportunities for training in context - Portugal, Gabriela (2018)
Educational interactions between adults and children are essential in any learning process,but have a crucial role in early childhood education. Given the importance of the quality of the interactions in early childhood education for the well-being, development and learning of children, we present a proposal for analyzing children’s living experiences and adult style, through child and adult engagement scales. These observation tools are particularly useful for training, professional development and improvement of teachers pedagogical practice. In this article the observation scales’ contribution to training in context is evidenced through a series of testimonials from educators who, by reflection and attention given to child experience and their own style, experienced professional development and consequent improvement in the quality of their interaction and on the educational offer.